Komunikasi Eco-Dialogue dalam Pembangunan Berkelanjutan Toll Semarang-Demak - Muhammad Yusuf Firdiansyah; Rahmawati Zulfiningrum (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2026)
Sustainable infrastructure development requires not only technical solutions but also effective environmental communication to balance environmental protection, social legitimacy, and community welfare. This study examines how Eco-Dialogue communication supports the sustainable development of the Semarang–Demak Toll Road Section 1, a National Strategic Project integrating a toll road and sea wall for tidal flood mitigation. A qualitative single instrumental case study was conducted using semi-structured interviews, observations, and document analysis involving nine informants representing government agencies, project contractors, local authorities, and fishing communities. Data were analyzed through the Miles et al. interactive model and pattern matching based on Cox's Environmental Communication framework. The findings reveal that Eco-Dialogue operates through seven interconnected communication domains that collectively shape stakeholder relationships and sustainable development outcomes. Environmental rhetoric strengthened the project's legitimacy through a tidal-flood mitigation narrative, while participation, collaboration, and community-based risk communication enhanced social acceptance and conflict resolution. However, environmental education remained fragmented because of institutional divisions of responsibility, limiting community adaptive capacity. The study introduces Eco-Dialogue as a novel analytical perspective that integrates Environmental Communication with Sustainable Development by conceptualizing communication as a continuous process of dialogue, negotiation, collaboration, and shared meaning-making in strategic infrastructure governance. The findings extend the application of Environmental Communication theory beyond conservation contexts and highlight the importance of institutional coordination, inclusive stakeholder participation, and continuous environmental education to strengthen the sustainability of future infrastructure projects. Keywords: Eco-Dialogue, Environmental Communication, National Strategic Project, Semarang Demak Toll Road Section 1, Sustainable Development.